2008
DOI: 10.1007/s12221-008-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of scouring on the wettability of keratin fibers before plasma treatment

Abstract: The present paper studies the wetting behavior and shrink-resistance of keratin fibers prepared by solvent extraction or by industrial-like surfactant washing as well as their response to plasma treatments. The results obtained reveal that keratin fibers can be prepared by surfactant washing instead of using solvents, which will allow carrying out research studies in closer conditions to the industrial reality, and indeed in a much economic and environmentally friendly way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…Surface functionalization of polymer fibers with oxygen moieties from low temperature plasmas is associated with improved wettability,36, 44, 49 while the presence of PDMS softeners on the surface of textiles is related to low wettability 52. Variations in superficial chemistry of the fibers are closely linked with their wetting properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface functionalization of polymer fibers with oxygen moieties from low temperature plasmas is associated with improved wettability,36, 44, 49 while the presence of PDMS softeners on the surface of textiles is related to low wettability 52. Variations in superficial chemistry of the fibers are closely linked with their wetting properties.…”
Section: Resultsmentioning
confidence: 99%
“…Power supply was kept constant at 100 W while gas flow was studied in the range between 5 and 15 L · min −1 , plasma treatment time between 1 and 5 min and gas pressure between 800 and 1 200 mT. To minimize the ageing process of the samples, post‐treatments like fabric impregnation and surface analysis were carried out right after plasma treatment of the fabrics 35, 36, 44, 45. PA 66 fabrics were laid flat on the ground of the reactor, as described in Figure 2, so that only one side of the sample was directly exposed to the plasma treatment although it can be considered that the plasma species may penetrate through the loose knit fabric structure and modify both sides of the material.…”
Section: Methodsmentioning
confidence: 99%
“…Not solely the chemical structure but additionally the roughness of the surface is affected by the plasma treatment; this also might change the wettability of the surface [17]. It has also been demonstrated that wetting of biological tissue might be changed by low-temperature radio frequency plasma [18] [19] [20]. Cold (nonequilibrium) radiofrequency plasma treatment of biological objects becomes a very important tool for modification of their chemical and physical properties [18] [19] [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, low-pressure plasma treatments with gases such as air, helium, nitrogen and oxygen have been used to improve the surface wettability and the dyeing properties of different textiles [15][16][17][18]. Moreover, in the case of wool, they have been employed to enhance its shrink resistance [19][20][21][22][23][24] and its anti-pilling properties [25].…”
Section: Introductionmentioning
confidence: 99%